Coverage of education and training of traumatic brain injury-induced growth hormone deficiency in US residency and fellowship programs: a cross-sectional study - Javier Cárdenas; Nicky Kelepouris; Radhika Adiga; Kevin C. J. Yuen (BMC Medical Education, 2024)
Abstract Background Hypopituitarism, including growth hormone deficiency (GHD), is a common sequela of traumatic brain injury (TBI). This study explored the coverage of education and training of TBI-induced hypopituitarism in general and GHD in particular, in postgraduate program curricula to identify knowledge gaps and opportunities. Methods An online survey and qualitative interviews (focus groups) were conducted among endocrinology, neurology, and physiatry postgraduate program directors in the United States (US). The study received an IRB exemption. Results A total of 419 fellowship and residency programs were invited to participate; 60 program directors completed the survey and 11 of these participated in the focus groups. About half of the respondents considered TBI-induced hypopituitarism important or fairly important to include in the curriculum, and nearly two-thirds considered it an appropriate training component. Neurology program directors considered education regarding hypopituitarism following TBI less important and relevant for their curricula compared with endocrinology and physiatry program directors. About half (53%) of the programs responded that they included TBI-induced pituitary disorders in their curricula. About two-thirds (68%) of endocrinology programs, compared with only one-quarter (25%) of neurology programs, covered TBI-induced pituitary disorders. Respondents identified multiple barriers to expanding hypopituitarism following TBI in the curriculum, including the rarity of condition and lack of time/room in the curriculum. Respondents reported that consensus clinical guidelines and the availability of more data on TBI-induced hypopituitarism, including GHD, would greatly impact the development of educational curricula on this topic. Conclusions To improve the management of TBI-induced hypopituitarism, education and training should be expanded in US fellowship and residency programs to prepare trainees to effectively screen, diagnose, and treat TBI-induced hypopituitarism, including GHD.